Biomedical engineering systems and technologies : 4th International Joint Conference, BIOSTEC 2011, Rome, Italy, January 26-29, 2011, Revised Selected Papers - Filipe, Joaquim; Gamboa, Hugo; Fred, Ana (Communications in Computer and Information Science, 2013)
This book constitutes the thoroughly refereed post-conference proceedings of the 4th International Joint Conference on Biomedical Engineering Systems and Technologies, BIOSTEC 2011, held in Rome, Italy, in January 2011. The 27 revised full papers presented together with one invited lecture were carefully reviewed and selected from a total of 538 submissions. The papers cover a wide range of topics and are organized in four general topical sections on biomedical electronics and devices; bioinformatics models, methods and algorithms; bio-inspired systems and signal processing; health informatics.